Specific needs of families of young adults with profound intellectual disability during and after transition to adulthood: What are we missing?. (July 2017) - Gauthier-Boudreault, Camille; Gallagher, Frances; Couture, Mélanie
Highlights: Lack of transition planning services and inter-institutional collaboration. Parents' occupational imbalance due to the obligation to reduce workload. Decrease in young adults' capabilities and increase of behavioural difficulties. Importance to offer material, informative, cognitive, and emotional support. Need to create solutions adapted to reality of families of youth with profound ID. Abstract: Introduction: At the age of 21, the trajectory of services offered to youth with profound intellectual disability (ID) change significantly since access to specialised services is more limited. Despite the desire of parents to avoid any impact on their child, several factors can influence the course of this transition. However, there is little research on facilitators and obstacles to the transition to adulthood, and impacts on people with a profound ID. It is therefore difficult to provide solutions that meet their specific needs. Objective: The study aimed to document the needs of parents and young adults with profound ID during and after the transition to adulthood by exploring their transitioning experience and factors that influenced it. Method: Using a descriptive qualitative design, two individual semi-structured interviews were conducted with fourteen (14) parents of young adults aged between 18 and 26 with a profound ID. Results: At this point, many material, informative, cognitive and emotional needs of young adults and their parents are not met. Obstacles, mainly organisational, persist and result in a particularly difficult transition to adulthood experience. Conclusion: By knowing the specific needs of these families, it is possible to develop and implement solutions tailored to their reality. What the papers adds?: The transition to adulthood is a critical period for families with young adults with an intellectual disability (ID), a reality observed internationally. Current literature on all levels of ID suggests some barriers to transition that lead to negative impacts on both parents and young adults with ID. However, presently, very little research exists on the reality of families of young adults with profound ID and factors influencing transition to adult life. Most of studies target people with mild to moderate ID. Considering the significant disabilities of people with profound ID, it is possible to imagine that their experience of transition will be even more difficult and they will present specific needs. The lack of understanding of these needs makes it difficult to introduce solutions tailored to their reality. The results of this current study suggest that many needs of young adults with profound ID and their parents are not met despite existent transition planning services. Transition to adulthood seems particularly difficult for these families who face many challenges. Parents in this study proposed different obstacles during transition to adulthood that could be improved for creation of future solutions adapted to their reality.